EFEKTIVITAS PEMUNGUTAN RETRIBUSI DAERAH PADA ORGANISASI PERANGKAT DAERAH DI PROVINSI BENGKULU - Yunita Asriyani Sari; Abdullah (JURNAL FAIRNESS, 2022)
The title of this research is “Efektivitas Pemungutan Retribusi Daerah pada Organisasi Perangkat Daerah di Provinsi Bengkulu”. The objective of this research was taking the description about region retribution in Bengkulu city. The significance of this research was giving the information in the affectivities of taking region retribution on the OPD in Bengkulu province and can add the knowledge about the taking region retribution on the OPD in Bengkulu province. For the academician, it could be the reference and consideration to increase the income and have the new potential in the region retribution sector toward the income of Bengkulu province and this research could become a reference for the advance research. The methodology of this research was qualitative research. This research had been done since January 2019 up to Juny 2019 as the location survey, collecting the data, and analysis data. This research had been done to some of government instances in the Bengkulu province. The technique of collecting data was by using interview, observation, and documentation. Based on the analysis which had been done, so the result was the taking of region retribution in this province was effective.  The factors those made this was; the official on the related instances was sufficient; there was involvement of the leader in each instances actively controlled the activities of taking region retribution in Bengkulu province; there was cooperative as team so that the instances did not have problem in reporting and storing of the region retribution in the related instances. Based on the research results, so the researcher suggested that for the Badan pengelola Keuangan Daerah Provinsi Bengkulu, it would be better to increase the monitoring by checking suddenly or period, increase the monitoring processes, giving punishment for them those always arrear in storage their duty then increase the tax payment and the service which was given by the government instances. The further researches were suggested to take new side of the region retribution implementation and the quality of service by involving some of variables, such as the involvement management by involving government instances which more extensive in the Bengkulu province.